Controllable syntheses and magnetic properties of novel homoleptic triple-decker lanthanide complexes. Issue 35 (21st August 2019) - Gao, Feng; Wang, Lei; Zhu, Guang-Zhou; Liu, Yu-Han; Yang, Han; Li, Xiang; Yang, Ke
Abstract : A class of novel triple-decker lanthanide complexes have been continuously designed and synthesized based on a Schiff base ligand Cl-salphenH2 and precursors [(acac)4 Ln2 (L)]. The results reveal Dy complex behaves as a typical SMM with intermetallic ferromagnetic interaction. Abstract : Four novel homoleptic triple-decker lanthanide complexes, [Ln2 (L)(Cl-salphen)2 ]·0.5ClCH2 CH2 Cl (Ln 3+ = Gd 3+ (1 ), Ho 3+ (2 ), Tb 3+ (3 ), and Dy 3+ (4 )), have been designed and synthesized based on a Schiff base ligand N, N ′-bis(5-chlorosalicylidene)- o -phenylenediamine (Cl-salphenH2 ) and the building blocks [(acac)4 Ln2 (L)]; these complexes were derived from a closed-macrocyclic ligand (H2 L) obtained by the [2 + 2] template condensation of 2, 6-diformyl-4-methylphenol and 1, 3-diaminopropane in the presence of lanthanide acetylacetonates. Single-crystal X-ray analyses show that central Ln 3+ ions adopt distorted square antiprism conformations with D 4d symmetry. Theoretical analysis and magnetic measurements reveal that Dy complex4 behaves as a typical SMM with the characteristics of slow magnetic relaxation behavior and intermetallic ferromagnetic interaction.